Pediatric Microsurgery in the Reconstruction of Complex Posttraumatic Foot and Ankle Defects: A Long-Term Follow-Up with a Comprehensive Review of the Literature - Elbatawy, Amr; Elgammal, Mohammed; Zayid, Tarek; Hamdy, Abdelnaser; Ouf, Mohamed Osama; Ismail, Hany; Sholkamy, Khallad; Malik, Mohammad; Zidan, Serag M.; Ayad, Wael (Journal of Reconstructive Microsurgery, 2020)
Background Lower limb reconstruction is a well-recognized challenge to the trauma or plastic surgeon. Although techniques and outcomes in the adult population are well documented, they are less so in the pediatric population. Here, we present our experience in the management of posttraumatic foot and ankle defects with free tissue transfer in children.Methods We performed a retrospective analysis of 40 pediatric patients between the ages of 3 and 16 from 2008 to 2016 who underwent foot and ankle soft tissue reconstruction. Any patient who underwent reconstruction for any reason other than trauma was excluded. Data were collected on operative time, free tissue transfer type, use of vein grafts, length of hospital stay, and postoperative morbidity. Also, a comprehensive systematic literature review was completed according to the PRISMA protocol for all previous reports of foot and ankle reconstruction in the young age group with free tissue transfer.Results Of our 40 patients, 23 were males and 12 females, free tissue transfer was used to reconstruct primarily the dorsum (71%), heel (11%), medial (9%), and lateral (3%) aspect of the foot. The anterior tibial artery was the predominant recipient vessel for anastomosis (77%). Mean inpatient stay was 9 days and our complication rate was 20%, primarily of superficial infection treated with antibiotic therapy. The review of the literature articles is completely analyzed in detail.Conclusion The need for durable coverage of exposed joints, tendons, fractures, or hardware makes the free flap particularly well suited to trauma reconstruction of the foot and ankle. The lack of underlying vascular disease in this patient group allows for low complication rates. Our study evidences the safety and positive long-term outcomes of free tissue transfer for the reconstruction of huge sized-soft tissue defects of the foot and ankle in children.
Keywords: foot reconstruction; pediatric microsurgery; free tissue transfer